Difference between revisions of "2021 AMC 10B Problems/Problem 15"
(→Solution 5) |
|||
Line 37: | Line 37: | ||
==Solution 5== | ==Solution 5== | ||
The equation we are given is <math>x+\tfrac{1}{x}=\sqrt{5}...</math> Yuck. Fractions and radicals! We multiply both sides by <math>x,</math> square, and re-arrange to get <cmath>x^2+1=\sqrt{5}x \implies x^4+2x^2+1=5x^2 \implies x^4-3x^2+1=0.</cmath> Now, let us consider the expression we wish to acquire. Factoring out <math>x^3,</math> we have <cmath>x^3\left(x^8-7x^4+1\right) = x^3\left(x^8+2x^4+1-9x^4\right).</cmath> Then, we notice that <math>x^8+2x^4+1=\left(x^4+1\right)^2.</math> Furthermore, <cmath>x^4+1=3x^2 \implies \left(x^4+1\right)^2=x^8+2x^4+1=9x^4.</cmath> Thus, our answer is <cmath>x^3\left(9x^4-9x^4\right) = x^3 \cdot 0 = \boxed{\textbf{(B)}} ~ 0.</cmath> | The equation we are given is <math>x+\tfrac{1}{x}=\sqrt{5}...</math> Yuck. Fractions and radicals! We multiply both sides by <math>x,</math> square, and re-arrange to get <cmath>x^2+1=\sqrt{5}x \implies x^4+2x^2+1=5x^2 \implies x^4-3x^2+1=0.</cmath> Now, let us consider the expression we wish to acquire. Factoring out <math>x^3,</math> we have <cmath>x^3\left(x^8-7x^4+1\right) = x^3\left(x^8+2x^4+1-9x^4\right).</cmath> Then, we notice that <math>x^8+2x^4+1=\left(x^4+1\right)^2.</math> Furthermore, <cmath>x^4+1=3x^2 \implies \left(x^4+1\right)^2=x^8+2x^4+1=9x^4.</cmath> Thus, our answer is <cmath>x^3\left(9x^4-9x^4\right) = x^3 \cdot 0 = \boxed{\textbf{(B)}} ~ 0.</cmath> | ||
+ | ~peace09 | ||
== Video Solution by OmegaLearn (Algebraic Manipulations and Symmetric Polynomials) == | == Video Solution by OmegaLearn (Algebraic Manipulations and Symmetric Polynomials) == |
Latest revision as of 14:52, 19 April 2021
Contents
Problem
The real number satisfies the equation . What is the value of
Solution 1
We square to get . We subtract 2 on both sides for and square again, and see that so . We can divide our original expression of by to get that it is equal to . Therefore because is 7, it is equal to .
Solution 2
Multiplying both sides by and using the quadratic formula, we get . We can assume that it is , and notice that this is also a solution the equation , i.e. we have . Repeatedly using this on the given (you can also just note Fibonacci numbers),
~Lcz
Solution 3
We can immediately note that the exponents of are an arithmetic sequence, so they are symmetric around the middle term. So, . We can see that since , and therefore . Continuing from here, we get , so . We don't even need to find what is! This is since is evidently , which is our answer.
~sosiaops
Solution 4
We begin by multiplying by , resulting in . Now we see this equation: . The terms all have in common, so we can factor that out, and what we're looking for becomes . Looking back to our original equation, we have , which is equal to . Using this, we can evaluate to be , and we see that there is another , so we put substitute it in again, resulting in . Using the same way, we find that is . We put this into , resulting in , so the answer is .
~purplepenguin2
Solution 5
The equation we are given is Yuck. Fractions and radicals! We multiply both sides by square, and re-arrange to get Now, let us consider the expression we wish to acquire. Factoring out we have Then, we notice that Furthermore, Thus, our answer is ~peace09
Video Solution by OmegaLearn (Algebraic Manipulations and Symmetric Polynomials)
~ pi_is_3.14
Video Solution by Interstigation (Simple Silly Bashing)
~ Interstigation
Video Solution by TheBeautyofMath
Not the most efficient method, but gets the job done.
https://youtu.be/L1iW94Ue3eI?t=1468
~IceMatrix
See Also
2021 AMC 10B (Problems • Answer Key • Resources) | ||
Preceded by Problem 14 |
Followed by Problem 16 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 | ||
All AMC 10 Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.